A viúva de Éfeso e outros contos - Chaves, Gilberto Collares (2013)
This dissertation belongs to an area that became popular very recently in Brazil: Creative Writing. I set out to work within this area on the elaboration of a storybook. The book " The Widow of Ephesus and other tales " tries to approach a fine line between reality and fiction. I will attempt to shorten these differences including in its fiction the theoretical work in this dissertation. I started by fictionalizing the author himself stipulating an alias as the author of the book. This author is already dead and his post-mortem books are to be edited by also a fictional editor. This editor found some notes after the death of the author, and with these notes I was unable to create theoretical and fictional material with all the creative process by the author in question, always having a distance created by a witness narrator (editor). In fictional form, I was able to bring out some theoretical questions about the creative process in the actual body of fiction within the creative text . The editor participates in the structure of the book, by observing his works from outside, (such as the included editor and friend of the author beyond a critical works). So, this is the character who organizes the editor s notes, post-mortem anthology of the author (fictional core of the stories) and also the appendix of editing: a biography and an essay. With these three literature genres biography, essay and short stories, although the first two are included as fiction in the dissertation, I could draw a link between work and life, factual reality and fantasy, and between transcendent image and logic imposed by reasoning. Yet to achieve a greater connection between reality and fiction, there is an ambiguous relation between editor and author constructing while the reader can walk through the three genres in question. This emotional connection will give closure to the proposal of approximation between reality and fiction.